Villain or scapegoat? Elephants and academic achievement of pupils and schools in Trans Mara District, Kenya. Issue 4 (8th February 2022) - Nyumba, Tobias Ochieng; Leader‐Williams, Nigel
Abstract: Improving human capital through quality education remains a global and national priority, particularly for developing countries. Academic performance is the standard indicator of a successful acquisition of the knowledge, skills, and attitudes for improving human capital. However, recent data, particularly in wildlife areas shows that pupils often perform poorly on academic tests in low‐income countries. This study aims to determine the impact of elephants on academic performance in Trans Mara District, Kenya. We use data from 137 schools and 749 pupils who wrote the Kenya Certificate of Primary Education between 2010 and 2014, and 15 key informants. We used descriptive statistics to analyze and interpret our data. Results show that locating a school outside the elephant range positively contributed to higher mean scores compared to ethnicity, pupil–teacher ratio and gender. Whereas day facilities only strongly contributed to lower scores compared to examination entry, age of the pupil, and ethnicity. The study places elephants on both ends of the villain‐scapegoat continuum since their presence alone does not make a major contribution to poor academic performance in the Trans Mara District. We recommend providing cheaper and accessible transport to pupils, expanding both day and boarding facilities, establishing additional schools closer to pupils within elephant range to reduce the distances to school. These initiatives must be linked to the conservation of elephants as a suit of direct incentives for coexisting with elephants.